REVITALISASI PENDIDIKAN KARAKTER PADA ANAK USIA DINI UNTUK MENCIPTAKAN GENERASI UNGGUL - Leni Nurmiyanti (JECIES: Journal of Early Childhood Islamic Education Study, 2021)
Activating the national character of the nation’s generation from an early age in an are that is developing so rapidly is a prosess that requires seriousness and collective awareness. Characrter education is a part that must be built since early childhood, this period is a golden age for children to be given a stimulus in coaching, learning, understanding and character building which will later become the main capital for them in the future. Children are the next generation who will fight for and defend their nation, thus of course it is very important for all elements of society to be responsible for creating a generation of hope for a nation with quality and character.            The creation of a superior generation that will be able to build an advanced civilization is certainly not an easy thing. It takes seriousness and consistency in supporting the educational prosess that will be given to the nation’s generation. The prosess of early childhood education must be developed and planned with a good planned, good organized pattern of education. The educational prosess obtained by the nation’s generation is of course a prosess that runs continuously and continues until the child is an adult, the prosess of shaping the future of the nation will certainly require time and an interrelated struggle between elements of society. Collective awareness and high willingness will help facilitate the educational prosess of children as the nation’s future generations.